Quality of registration of dental medical records in a health center in the city of Ica, Peru - Hernández Espino, Raúl (2023)
Objective: The objective of this study was to assess the quality of dental medical record keeping at a health center in the city of Ica, Peru. Material and methods: We conducted a descriptive study using a quantitative, non-experimental, observational, cross-sectional, and retrospective approach. The sample comprised 212 medical records that were evaluated according to Health Technical Standard No. 029-MINSA/DIGEPRES-V.02. This standard, approved by Ministerial Resolution No. 502-2016/MINSA, allowed for the assessment of various aspects with corresponding scores. After tallying the scores obtained, we ranked the records accordingly. Results: The findings revealed that among the medical records at the health center in the city of Ica, 53.8 % demonstrated a need for improvement in quality, 42 % exhibited satisfactory quality, and 4.2 % displayed poor quality. Conclusions: The medical records at the Ica health center are in need of improvement for 53.8 % of cases.